2012
DOI: 10.1007/s10554-012-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose exposure of patients undergoing 320-row cardiac CT for assessing coronary angiography and global left ventricular function

Abstract: A 320-row multidetector CT provides the capability for prospective electrocardiogram (ECG)-gated coronary CT angiography (CTA) and tube current modulated cardiac function assessment (CFA). We assessed and compared the effective radiation dose of these two modes. On a prospective basis, we performed ECG-gated cardiac CT on 119 patients (87 were males). For heart rates (HRs) /=80 bpm were scanned wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…ED values of multi-slice computed tomography coronary angiography (CTCA) with the use of retrospective ECG-gating -representing noninvasive CA -are reported to vary from 8 to 28 mSv [4, 20,21] and yield the considerable calculated LAR of cancer incidence for a representative 50-year-old subject with a range between 0.10 and 0.17 % for males and between 0.23 and 0.37 % for females [22]. The use of automatic dose control reduced the ED in chest scans by 36 % [23], and in conformity with actual recommendations [24], ECG-triggered, singleand two-heartbeat CTCA enabled lower EDs of 2.2 to 8.6 mSv, without affecting diagnostic performance [21,[25][26][27]. For the specific subgroup of non-obese patients with a low and stable heart rate, furthermore, values even on the submillisievert level for CTCA have been achieved [28].…”
mentioning
confidence: 78%
“…ED values of multi-slice computed tomography coronary angiography (CTCA) with the use of retrospective ECG-gating -representing noninvasive CA -are reported to vary from 8 to 28 mSv [4, 20,21] and yield the considerable calculated LAR of cancer incidence for a representative 50-year-old subject with a range between 0.10 and 0.17 % for males and between 0.23 and 0.37 % for females [22]. The use of automatic dose control reduced the ED in chest scans by 36 % [23], and in conformity with actual recommendations [24], ECG-triggered, singleand two-heartbeat CTCA enabled lower EDs of 2.2 to 8.6 mSv, without affecting diagnostic performance [21,[25][26][27]. For the specific subgroup of non-obese patients with a low and stable heart rate, furthermore, values even on the submillisievert level for CTCA have been achieved [28].…”
mentioning
confidence: 78%
“…In combination with high gantry rotation speed/temporal resolution, these scanners allow single beat axial acquisition with a static table. [38][39][40][41] The image reconstruction algorithms used for CT image reconstruction can further influence the choice of scan factors and thus the associated radiation dose. Most modern CT scanners are increasingly employing sophisticated iterative reconstruction (IR) techniques as compared with the previously used filtered back projection (FBP) algorithms, which are less computationally demanding.…”
Section: Other Scanner-related Factorsmentioning
confidence: 99%
“…9 Various studies have reported radiation doses associated with the use of wide detector array MDCT scanners for CCTA ranging from 4.4 to 15 mSv. 9,38,39,41,78,79 In a single study with second-generation wide-volume 320-detector row MDCT, Chen et al 40 reported a substantially low radiation dose for CCTA examinations (0.9 mSv; interquartile range 0.6 to 1.7 mSv).…”
Section: Single Heart Beat Scan With Wide Detector Arraymentioning
confidence: 99%
“…Image quality can be impaired with heart rates greater than 60 beats per minute and by irregular heart rhythms such as AF. Also of potential concern, CCT is associated with a small dose of radiation exposure 13,14 and may be contra-indicated in patients with allergies to iodinated contrast or significant renal impairment.…”
Section: Echocardiographymentioning
confidence: 99%